A new species within the Enteromius kerstenii complex (Actinopterygii, Cyprinidae, Smiliogastrinae) from south-western Ethiopia - Englmaier, Gernot K.; Chai, Min; Wubie, Alemayehu; Collins, Rupert A.; Getahun, Abebe (Zootaxa, 2024)
A new species of small-sized smiliogastrin barb, Enteromius gamo sp. nov., is described from tributaries to lakes Abaya and Chamo in south-western Ethiopia. The new species belongs to a readily diagnosable group commonly identified as E. kerstenii, exhibiting a thickened and serrated last unbranched ray in the dorsal fin, a low number of scales in the lateral series (≤ 27), and a yellow, orange or reddish blotch on operculum. Pairwise genetic distances between the new species from Ethiopia and specimens of E. kerstenii from close to the type locality in north-eastern Tanzania were 7.5–8.3 % (COI) and 8.9–10.1 % (cytb). Enteromius gamo sp. nov. is morphologically distinguished from E. kerstenii and all examined congeners from Tanzania, Kenya, and Uganda primarily by short anterior (15.8–35.1 %, mean 27.4 %, of snout length) and posterior (63.2–95.7 %, mean 81.0 %, of snout length) barbels. The new species is known only from wetlands and side channels of rivers (Hare, Sile, and Sago) along the western shores of lakes Abaya and Chamo.